From Desecularization to Sacralization of the Political Language: Religion and Historiosophy in Vladimir Putin’s Preparations for War - Składanowski, Marcin; Smuniewski, Cezary (Verbum Vitae, 2022)
This article aims to analyze religious and mystical elements contained in Putin’s public statements by referring to selected examples characteristic of contemporary Russian identity politics. In order to demonstrate the importance of religious and mystical threads in Putin’s speeches, we chose five specific cases. The analysis of these statements indicates that religious and mystical motifs in Putin’s language are an attempt at self-creation for the purpose of domestic policy. We claim that this self-creation is more of an effort to strengthen Putin’s public support than proof that he borrows patterns for shaping Russia’s political life from the Russian religious and political tradition. Putin’s rhetoric is not so much a desire for an axiological renewal of Russian politics but an attempt to search for the new legitimization of the power system he created in confrontation with the West.